Rituximab plus HyperCVAD alternating with high dose cytarabine and methotrexate for the initial treatment of patients with mantle cell lymphoma, a multicentre trial from Gruppo Italiano Studio Linfomi - Merli, Francesco; Luminari, Stefano; Ilariucci, Fiorella; Petrini, Mario; Visco, Carlo; Ambrosetti, Achille; Stelitano, Caterina; Caracciolo, Francesco; Di Renzo, Nicola; Angrilli, Francesco; Carella, Angelo M.; Capodanno, Isabella; et al. (British journal of haematology, 2012)
Summary This study investigated the clinical activity and toxicity of R‐HCVAD‐AM [rituximab plus HyperCVAD (R‐HCVAD) alternating with high‐dose cytarabine and methotrexate (AM)] in patients with newly diagnosed Mantle Cell Lymphoma (MCL). Patients aged ≤70 years with confirmed MCL received four alternating cycles each of R‐HCVAD and AM. Patients who obtained a partial response proceeded to autologous stem cell transplant. Sixty‐three patients were enrolled and 60 were fully eligible. Median age was 57 years (22–66); 60%, 33% and 7% were classified at low (L)‐, intermediate (I)‐ or high (H)‐risk, respectively, according to the MCL International Prognostic Index (MIPI). Only 22 patients (37%) completed the four cycles and three patients died during therapy. Overall response and complete response rates were 83% and 72% respectively. After a median follow‐up of 46 months (range 1–72) the estimated 5‐year overall survival (OS) and progression‐free survival rates were 73% [95% confidence interval (CI) 59–83%], and 61% (95%CI 45–73%) respectively. MIPI maintained the prognostic value with an estimated 5‐year OS of 89%, 80% and 24% for L, I, and H groups respectively (P < 0·001). This multicentre study confirms that R‐HCVAD‐AM is an active regimen for the initial treatment of patients with MCL, but is associated with significant toxicity.